Implementation Of The Second Preceptive Of Pancasila To Overcome The Crisis Generation Z Identity In The Globalization Era - Dien Putri Aulia; Marcella; Yolanda Eben Haezer; Harum Amarrissa Harsojoh; Agoes Dariyo (Penerbit Jurnal Indonesia, 2025)
In the era of globalization, Generation Z is faced with rapid social, cultural, and technological changes. This can have a significant impact on values and identity in daily life. However, the sophistication of technology does not always have a positive impact; there are also negative ef ects experienced by Generation Z, namely an identity crisis. Therefore, this research aims to understand the application of Pancasila values, particularly the second principle, in the daily lives of Generation Z in Indonesia and to evaluate the extent to which this application contributes to addressing the identity crisis in this generation. This research uses the literature review method, by reviewing and analyzing previously conducted research articles. The data collection technique used was through journal databases related to the targeted research topic. Research results show the importance of instilling Pancasila values through civic education, character education, and multicultural education to address the identity crisis in Generation Z, who are the future leaders that will realize Indonesia's goals and aspirations by instilling Pancasila values as the state ideology